The profile of heavy metals in surface and core sediments from Rambungan and Rayu rivers, Matang, Sarawak - Ammar Ubaidullah, Bin Rozali (Universiti Malaysia Sarawak, UNIMAS, 2012)
A study was carried out to determine the distribution of heavy metals in the surface and core sediments from Rambungan and Rayu Rivers, Matang. The surface and core sediment were collected from four sampling stations, namely ST1, ST2, ST3 and ST4. The sediments were analyzed for several heavy metals (Zn, Cd, Cu, Ni, Pb, Cr and As) by using atomic absorption spectrophotometer (AAS). All the stations were considered non-polluted from Zn, Cu and Pb. The distributions of Cr were moderately polluted. The distribution of As in ST1 and ST2 were moderately polluted, and in ST3 and ST4 were considered as heavily polluted, since the concentration values were very high. The study of profile of core sediment could illustrate the history of accumulation of heavy metals in the sediments. The evaluation of environmental status in the sampling stations could be done based on the level of heavy metals in the spatial sediments.